1970
DOI: 10.1111/j.1365-2141.1970.tb01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume Changes in Splenomegaly

Abstract: Summary. Blood volume changes have been measured in 65 patients with splenomegaly due to a miscellany of causes. The red‐cell mass is often normal despite the fact that anaemia is present, and the anaemia is in part due to sequestration of red cells in a splenic pool and haemodilution of the red cells in an expanded plasma volume. Both factors may be relieved by splenectomy although the ultimate prognosis is dependent on the primary disease present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Occasionally frank haemolytic anaemia may develop (Read, Sherlock, and Harrison, 1963;Pengelly and Jennings, 1971;Panush et al, 1973). With gross enlargement of the spleen in chronic liver disease a large pool of erythrocytes may be sequestered in the spleen thus reducing the effective extrasplenic red cell volume (Donaldson, McArthur, MacPherson, and Richmond, 1970). Finally there is the possibility that the splenic enlargement per se might be associated with an expansion of the plasma volume to give a haemodilutional anaemia (Toghill and Green, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally frank haemolytic anaemia may develop (Read, Sherlock, and Harrison, 1963;Pengelly and Jennings, 1971;Panush et al, 1973). With gross enlargement of the spleen in chronic liver disease a large pool of erythrocytes may be sequestered in the spleen thus reducing the effective extrasplenic red cell volume (Donaldson, McArthur, MacPherson, and Richmond, 1970). Finally there is the possibility that the splenic enlargement per se might be associated with an expansion of the plasma volume to give a haemodilutional anaemia (Toghill and Green, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The gross increase in plasma volume has now been shown to occur in many haematological disorders (Prankerd, 1963;Weinstein, 1964;Donaldson et al, 1970) and also in the various types of tropical splenomegaly as seen in Hong Kong (McFadzean, Todd, and Tsang, 1958), Uganda (Richmond, Donaldson, Williams, Hamilton, and Hutt, 1967), and New Guinea (Pryor, 1967a). The only common factor in this wide spectrum of diseases is the gross splenomegaly, and it is now clear that the degree of expansion of the plasma volume is directly proportional to spleen size (Pryor, 1967b;Blendis, Toghill, and Williams, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Pooling of erythrocytes in the splenic pulp functionally excludes a considerable volume of red cells from the main arteriovenous circulation (Prankerd, 1963) and the effective peripheral venous haematocrit may be further reduced by an apparent increase intheplasmavolume (Donaldson, McArthur, MacPherson, and Richmond, 1970). This paper records the blood volumes of 64 patients with splenomegaly due to haematological disorders, and describes serial changes in 12 of these patients in whom there were alterations in spleen size.…”
mentioning
confidence: 99%
“…In reports of two groups of patients with miscellaneous disor ders associated with splenomegaly a statistical relationship has been es Discussion tablished between pool size and spleen size [4,12]. However, P ettit et al [8], who measured total splenic red cell content, found it to be less in the lympho-proliferative disorders as compared with the myelo-proliferative diseases and regarded this as being due to replacement of the splenic cords by lymphoid tumour tissue.…”
Section: Splenic Pool Size In Myelo-and Lympho-proliferative Syndromesmentioning
confidence: 99%
“…The dependence of pool size and spleen size in various disease states during treatment or during pro gression of disease as shown in this work supports the concept of a splen ic pool caused by splenic enlargement rather than by a specific pathologi cal process. However, in some haemolytic anaemias the splenic pool may be disproportionately large [4].…”
Section: Splenic Pool Size In Myelo-and Lympho-proliferative Syndromesmentioning
confidence: 99%